Near-Infrared Data Acquisition for the VERITAS 2023 Iceland Field Campaign - Adeli, Solmaz; Garland, Stephen Patrick; Nunes, Daniel C.; Smrekar, Suzanne E.; Mueller, Nils; Domac, Akin; Alemanno, Giulia; Hamilton, Christopher W.; Pedersen, Gro; Cascioli, G.; Althaus, Christian; Hauber, Ernst; et al. (2024)
The composition of lava fields on Venus and their alteration state are poorly constrained. The Venus Emissivity Mapper (VEM) [1, 2] on board NASAs VERITAS [3] and its twin VenSpec-M on ESAs EnVision will observe the surface of Venus in the NIR range through five atmospheric windows covered by six spectral bands (0.86 to 1.2 um). These will enable studying the spectral characteristics of the Venusian surface, as well as lava types and possible alteration processes. To prepare for these missions and deepen our understanding of the emissivity spectral characterization of various volcanic rocks, we developed a field camera system analogous to VEM, named VEMulator2.0 [4], and have undertaken in-situ measurements during the VERITAS expedition in Iceland, early August 2023. We relate these data to emissivity spectra of field samples acquired in the Venus chamber at the Planetary Spectroscopy Laboratory (PSL) of DLR-Berlin [1].